Urgency of Sufism in Solving Millennial Generation Moral Problems - MUHJA , Zainal Abidin; WIJAYA, Meliani Indria (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2023)
The escalating concerns surrounding moral issues have given rise to a disquieting atmosphere. Curiously, an individual’s recognition of moral deficiencies does not necessarily translate into heightened self-awareness of their own virtuous conduct. The tumultuous and emotionally charged states of hearts often propel certain individuals towards actions that contravene the tenets of Islam. In response, this study aims to outline a strategy for addressing emotional instability and unbridled emotions among students through the integration of Sufi science. Employing a qualitative and literature-based approach, this research draws upon primary data derived from documentary and library materials encompassing Sufism’s scholarly corpus, with triangulation ensuring data collection, analysis, presentation, and conclusion-drawing rigor. The ability of Sufism to instill serenity and self-discipline, as seen from the discourse findings, emphasises its contemporary relevance. Within Sufi tenets, the significance of moral education emerges as pivotal as it navigates humanity towards ethical pathways, acting as a bulwark against moral decay, spiritual tumult, and moral ascendancy. Presently, there exists a pressing need to reevaluate and recontextualize the spiritual principles intrinsic to Sufism, fostering a persona that harmonises both ritualistic observance and moral rectitude. This endeavour is imperative to resolving the multifarious challenges that beset the modern era.